2016
DOI: 10.1111/papr.12496
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prevalence, Outcomes, and Help‐seeking Behavior of Chronic Pain in an Aging Population Over the Last Decade

Abstract: The prevalence of neuropathic pain in Hong Kong is high and is described here for the first time. The number of chronic pain sufferers has tripled in the past decade. Significant changes in the patterns and help- seeking behavior of chronic pain sufferers are also seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
0
17
0
2
Order By: Relevance
“…Data from general population studies have shown the prevalence of chronic pain in the elderly can be as high as 55% after the age of 60 years67 and as high as 62% after the age of 75 years 56. The prevalence of chronic pain remains the same in the age group 60–74 and the age group >75, however the data for this statement are limited 67…”
Section: Epidemiologymentioning
confidence: 99%
“…Data from general population studies have shown the prevalence of chronic pain in the elderly can be as high as 55% after the age of 60 years67 and as high as 62% after the age of 75 years 56. The prevalence of chronic pain remains the same in the age group 60–74 and the age group >75, however the data for this statement are limited 67…”
Section: Epidemiologymentioning
confidence: 99%
“…Individuals with chronic neuropathic pain were associated with more severe pain, longer duration of pain, pain in more body locations, lower quality of life, worse sleep quality, increased symptoms of anxiety and depression, and greater use of health care resources [ 3 , 4 , 7 9 ]. In a cross sectional telephone interview, we reported that the prevalence of pain with neuropathic characteristics (acute and chronic) was 9.03% in a Chinese population in Hong Kong [ 10 ]. In addition, 14.7% of Chinese patients suffering from chronic pain in Hong Kong had neuropathic characteristics [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 A recent study showed that 28.7% of people in Hong Kong have chronic pain. 2 This can be a major reason for reduced psychosocial function, impaired quality of life, and increased health care costs. 2 Spinal cord stimulation mainly targets neuropathic pain and has limited efficacy for nociceptive pain.…”
Section: Introductionmentioning
confidence: 99%
“…2 This can be a major reason for reduced psychosocial function, impaired quality of life, and increased health care costs. 2 Spinal cord stimulation mainly targets neuropathic pain and has limited efficacy for nociceptive pain. 1 Neuropathic pain is common in Hong Kong, affecting 9.03% of the total population and 14.7% of chronic pain sufferers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation